What is User Engagement? : A Systematic Review of 241 Research Articles in Human-Computer Interaction and Beyond - Jansen, Bernard J.; Guan, Kathleen W.; Salminen, Joni; Aldous, Kholoud Khalil; Jung, Soon-Gyo (ACM, 2025)
User engagement (UE) is widely discussed in HCI articles, but its definition, reliability, and application remain elusive. This research conducts a systematic literature review of 241 articles from 1993 to 2023 to analyze how UE is defined and measured within the domain of HCI. Our findings reveal significant definitional inconsistencies that hinder UE's practical application in HCI research and system design. Based on our findings, we recommend using UE as a categorical label rather than a unified construct until more systematic frameworks are established. We also highlight the need for divergent views of UE across HCI research communities as a valuable avenue to pursue. This divergent view approach can help HCI researchers focus on specific, measurable aspects of UE that align with specific community practices and norms. Our findings also suggest that until such a framework emerges, researchers should be aware of its limitations when using UE as a research construct.
Keywords: user experience; user interaction; user needs; user metrics; fi=Markkinointi|en=Marketing|